Convergence, Dynamics, and Geography of Economic Growth: The Case of Municipalities in Rio Grande do Norte, Brazil - Verner, Dorte; Tebaldi, Edinaldo (World Bank, Washington, D.C., 2013)
Analyses of municipal GDP growth in Rio Grande do Norte in the Northeast of Brazil during 1970-96 reveal that the cross-section dispersion of per capita income increased over time. Although the analysis indicates some spatial dependence in income, it is small and has a downward trend, indicating that the growth path is only weakly determined by geographical links in Rio Grande do Norte. Moreover, dynamic analyses based on the Markov chain transition matrix show that the probability of a municipality moving from a poor income class to a rich class is very small and vice-versa. Municipalities located in the middle-income class have high mobility, but there is no strong evidence indicating direction. Public policy should include assisting the rural families by providing them education and training that increases their opportunities for employment. There should also be policies to assist poor and unskilled migrants to integrate fully into the modern economy in the urban areas through skill development training and education.